Antimicrobial activity and mode of action of terpene linalyl anthranilate against carbapenemase-producing Klebsiella pneumoniae - Shun-Kai Yang; Khatijah Yusoff; Mokrish Ajat; Wai-Sum Yap; Swee-Hua Erin Lim; Kok-Song Lai (Elsevier, 2021)
Mining of plant-derived antimicrobials is the major focus at current to counter antibiotic resistance. This study was conducted to characterize the antimicrobial activity and mode of action of linalyl anthranilate (LNA) against carbapenemase-producing Klebsiella pneumoniae (KPC-KP). LNA alone exhibited bactericidal activity at 2.5% (V/V), and in combination with meropenem (MPM) at 1.25% (V/V). Comparative proteomic analysis showed a significant reduction in the number of cytoplasmic and membrane proteins, indicating membrane damage in LNA-treated KPC-KP cells. Up-regulation of oxidative stress regulator proteins and down-regulation of oxidative stress-sensitive proteins indicated oxidative stress. Zeta potential measurement and outer membrane permeability assay revealed that LNA increases both bacterial surface charge and membrane permeability. Ethidium bromide influx/efflux assay showed increased uptake of ethidium bromide in LNA-treated cells, inferring membrane damage. Furthermore, intracellular leakage of nucleic acid and proteins was detected upon LNA treatment. Scanning and transmission electron microscopies again revealed the breakage of bacterial membrane and loss of intracellular materials. LNA was found to induce oxidative stress by generating reactive oxygen species (ROS) that initiate lipid peroxidation and damage the bacterial membrane. In conclusion, LNA generates ROS, initiates lipid peroxidation, and damages the bacterial membrane, resulting in intracellular leakage and eventually killing the KPC-KP cells.